2002
DOI: 10.1103/physrevlett.89.247002
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Oscillations of Josephson-Vortex Flow Resistance inBi2Sr2Ca

Abstract: To study the Josephson-vortex system, we have measured the vortex-flow resistance as a function of magnetic field parallel to the ab plane in Bi(2)Sr(2)CaCu(2)O(8+y) single crystals. Novel periodic oscillations of the vortex-flow resistance have been observed in a wide range of temperatures and magnetic fields. The period of the oscillations corresponds to the field needed to add "one" vortex quantum per "two" intrinsic Josephson junctions. The flow velocity is related to a matching effect between the lattice … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
82
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 20 publications
(32 reference statements)
8
82
1
Order By: Relevance
“…Promising experiments in that direction were reported by Hirata et al 2 and shortly thereafter by Kakeya et al 3 and Hatano et al 4 These experiments all showed oscillations in the flux-flow voltage and flux-flow resistance when a large magnetic field ͑of order several Tesla͒ was applied parallel to the ab plane in the presence of a small bias current in the c-direction ͑of order a few percent of the critical current͒. The observed flux-flow voltage oscillations typically showed two different oscillation periods.…”
Section: Origin Of Flux-flow Resistance Oscillations Inmentioning
confidence: 80%
“…Promising experiments in that direction were reported by Hirata et al 2 and shortly thereafter by Kakeya et al 3 and Hatano et al 4 These experiments all showed oscillations in the flux-flow voltage and flux-flow resistance when a large magnetic field ͑of order several Tesla͒ was applied parallel to the ab plane in the presence of a small bias current in the c-direction ͑of order a few percent of the critical current͒. The observed flux-flow voltage oscillations typically showed two different oscillation periods.…”
Section: Origin Of Flux-flow Resistance Oscillations Inmentioning
confidence: 80%
“…Figs . The H 0 /2 JVFR oscillation, often observed in the S-shaped embedded structures, is known to originate from the interaction between a triangular vortex lattice and the edge potential for the vortex entry and exit at the junction boundaries [12,13]. The H 0 /2 oscillation in our sandwiched oscillator stack thus strongly indicates the formation of the triangular lattice in its low-bias static limit.…”
mentioning
confidence: 79%
“…Recently, the dynamic properties of this lattice in BSCCO have been the subject of extensive experimental research. [7][8][9] Quite typically, magnetic field oscillations of the flux flow voltage or the flux flow resistance with either a ⌽ 0 or a ⌽ 0 / 2 periodicity ͑in applied field times the layer area͒ has been observed. A straightforward explanation of such periodicities can be obtained by looking at the lattice structure.…”
Section: Introductionmentioning
confidence: 99%